An analysis of the extent to which monetary and non-monetary rewards motivate employees within a Chinese Financial-services SME - Zhang, Naidan (2017)
There have been many controversies related to the importance of monetary and non-monetary rewards on motivating employees. In order to help managers to motivate employees effectively, this research set up to analyze the extent to which monetary and non-monetary rewards motivate employees within a case company that is a Chinese Financial-services SME.